Information Theoretic Security 5th International Conference, ICITS 2011, Amsterdam, The Netherlands, May 21-24, 2011, Proceedings - Fehr, Serge (Security and Cryptology ;, 2011)
This book constitutes the refereed proceedings of the 5th International Conference on Information Theoretic Security, held in Amsterdam, The Netherlands, in May 2011. The 12 revised full papers presented together with 7 invited lectures were carefully reviewed and selected from 27 submissions. Understanding the minimal requirements for information-theoretic security is a central part of this line of research. Very attractive is the mathematical neatness of the field, and its rich connections to other areas of mathematics, like probability and information theory, algebra, combinatorics, coding theory, and quantum information processing, just to mention the most prominent ones.